Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1998)
Table of Content Supermarket History, Johan Grimonprez interviewed by Catherine Bernard Tracey Moffatt Moffat’s Australia (A Reconnaissance) by Adrian Martin A Stranger Within by Ewa Laker-Burcharth Elizabeth Peyton And Inverview with a Painter by Linda Pilgrim Unhappy Kings by David Rimanelli Interview with a Painter’s Model by Linda Pilgrim In Praise of Hands, Elizabeth Peyton’s Painting by Philip Ursprung A Tender Trap by Lisa Liebmann Wolfgang Tillmans Tillmans’s Memory Machine by Midori Matsui Concorde by Neville Wakefiled Come On Baby by Jen Budney Only Comments by Judith Nesbitt Wants Both. Tillmans’s Museum Presentation of his Photographs by Ulf Erdmann Ziegler David Shrigley, Insert The Virgin Has Descended the Stairs. Remarks on a Contemporary Parable by Bernard Marcadé A Dud, Les Infos de L’Enfer by Valeria Liebermann Acting Out – Learning from Los Angeles, Cumulus from America by Jennifer Blessing Cumulus from Europe by Yves Aupetitallot Roth on the Roades by Juri Steiner & Guido Magnaguagno.
Another picture by Wolfgang Tillmans shows three youths, their heads stacked as if on a totem pole. They are immersed in a mood of intense concentration, a string trio without instruments, whose performance consists solely of posing and smoking. Through his singular perception and the confidence he inspires, Tillmans challenges people, things and situations to divest moments of their facticity and transform them into ambiguous pictorial products. The power of the photographic image suffuses his subjects to the very core of their being. It is the irreality of mediated life that contributes substantially to the design of reality as a whole. This now familiar insight lends momentum to the confrontation in the newly discovered emotional potential of Elizabeth Peyton’s painting. The collective dream cast of characters in her pictures oscillates between absence and presence. But they are sensual regardless, if only because of their vital imaginative thrust. An act of sweet appropriation quickens the rouge on male skin. One of our authors expressed the wish to touch Peyton’s paintings, while the wayward impalpability of her representations retreats all the more into the background of his perception. What is the relationship of “anthro” to “socio”? Tracey Moffatt’s people act out psychologically charged situations of elemental implications. They appear to be abandoned or detached, and always precariously balanced on the edge of civilization. As if this alone were the place to penetrate the depths of human memory, as if civilization were a grand process that sterilizes what must not be remembered. Another issue has been completed and we look upon David Shrigley’s drawing on the last page of the Insert with a mixture of dismay and satisfaction…
boek
Keywords: Moffatt, Tracey; Tillmans, Wolfgang; Peyton, Elizabeth